Loneliness, Social Support Networks, Mood, and Well-Being among the Community-Dwelling Elderly, Mysore - Meghana Narendran; Renuka Manjunath; M. R. Narayana Murthy (Indian Journal of Medical Specialities)
Background: Humans are social beings. Older adults more commonly endorse social engagement than physical health when describing successful aging. Deficits in social support have been associated with a wide variety of adverse health outcomes in older age, ranging from physical health to depression and self-harm. In this study, we attempt to identify the relative contributions of subjective social isolation (loneliness) and objective social isolation, measured as support network type, to depression and well-being among the community-dwelling elderly. Therefore, the objective of the study was to estimate the prevalence of loneliness and depression and to know the relationship between social network type, loneliness, and depression among the community-dwelling elderly. Subjects and Methods: A cross-sectional study was done for a period of 6 months. Individuals aged 60 years and above were included and severely ill and bed-ridden patients were excluded from the study. Sampling method used was population proportion to size with sample size of 290. The participants were interviewed using a semistructured questionnaire, where demographic and personal data and social network pattern were collected. Depression was assessed using the Geriatric Depression Scale. Data were analyzed using Statistical Package for the Social Sciences Software, 22.0 version. Descriptive statistics like percentage, mean, and standard deviation were applied. Inferential statistical tests such as the Chi-square test were applied to find out the association and expressed it as statistically significant at a P value < 0.05. Results: Among the study participants, 44.3% were lonely, 19.4% felt hopeless, and only 38% felt satisfaction in life and happiness. "Suggestive Depression" was seen among 48.6% and "Persistent Depressive Mood" was seen in about 20.2% of participants. Loneliness explained the excess risk of depression in the widowed. Similarly, 38.2% had a nonintegrated social network and 32% had integrated social network who also reported being lonely. Conclusion: Loneliness and social networks both independently affect mood and well-being in the elderly, underlying a very significant proportion of depressed mood.